Changes in performance structure during group competitions in rhythmic gymnastics - Hökelmann, A.; Breitkreutz, T.; Liviotti, G. (World Congress of Performance Analysis of Sport IX, 2012)
Group competitions in Rhythmic Gymnastics are by characterised difficult body movement elements (jumps and leaps, balances, flexibilities and waves, pivots) and apparatus techniques of ball, hoop, ribbon, rope or clubs, plus an aesthetic and artistic aspect. Additionally, collaboration and synchronicity of the 5 gymnasts effect the group performance. Thus, performances in Rhythmic Gymnastics are influenced by quantitative and qualitative factors. Qualitative factors are difficult to analyse as they are highly dependent of subjective perceptions. Quantitative factors are more objective and as a consequence, more suitable for performance analysis. The aim of the study was to define tendencies in performance development in international elite level group competitions in Rhythmic Gymnastics and therefore, derive recommendations for the specific coaching process. Group finals of the World Championships 2009 (Mie, Japan), the European Championships 2010 (Bremen, Germany), and the World Championship 2011 (Montpellier, France) were analysed post-event, based on video footage. Videos were recorded at 25Hz and showed the entire gymnastics mat from the perspective of the jury desk. The analysis was performed utilising the notational software SimiScout (Simi GmbH, Germany) and Utilius vs. (CCC-Software, Germany). Finally, an explorative factor analysis was carried out to discover the most influencing factors in performance in Rhythmic Gymnastics. Factor analysis for the routines of the World Championships 2009 displayed that the performance structure of the routines were determined the most by the factors a) Synchronicity, b) Body Movement Elements and Number of Formation, and least determined c) Apparatus Techniques. For the European Championships 2010 it was found that the factors a) Body Movement Elements and Space Utilisation were the most determining for successful performances in this particular competition. Followed by the factors b) Apparatus Techniques and c) Synchronicity. The performance structure of the routines demonstrated at the World Championships 2011 tend to be determined by: a) Apparatus Techniques, b) Body Movements Elements and Synchronicity, and Space Utilisation. Concluding, it can be stated that the performance structure in the final routines during the last three international competitions in Rhythmic Gymnastics seem to be determined by the following main factors: Body Movement Elements, Apparatus Techniques, Synchronicity and Space Utilisation. However, due to the results of the factor analyses of the different routines it can be assumed that the mastery of the apparatus techniques become more important than the performance of body movement elements and synchronicity. As in 2009 the number of Formations and Synchronicity were two of the most determining factors of performance structure and these factors became less important in 2011. This may be due to the fact that formations and synchronicity are influencing each other. Most formations require synchronicity. As formations become less important than complex collaborations and interactions between the gymnasts, synchronicity also loses importance. Another change in performance structure in recent past years occurred in terms of body movement elements and apparatus techniques. As in 2009 apparatus techniques were the less determining factor. It became the most crucial in 2011. This can be justified by the limit of physical performances in terms of developing more difficult and complex body movement elements. These limits seem not to be reached for the mastery of original apparatus techniques until now.